Μ‐Opioid activation in the midbrain during migraine allodynia – brief report II. (1st June 2014) - Nascimento, Thiago D.; DosSantos, Marcos F.; Lucas, Sarah; van Holsbeeck, Hendrik; DeBoer, Misty; Maslowski, Eric; Love, Tiffany; Martikainen, Ilkka K.; Koeppe, Robert A.; Smith, Yolanda R.; Zubieta, Jon‐Kar; DaSilva, Alexandre F.
Abstract We investigated in vivo the allodynic response of the central μ‐opioid system during spontaneous migraine headaches, following a sustained pain threshold challenge on the trigeminal ophthalmic region. Six migraineurs were scanned during the ictal and interictal phases using positron emission tomography (PET) with the selective μ‐opioid receptor (μOR) radiotracer [11C]carfentanil. Females were scanned during the mid‐late follicular phase of two separate cycles. Patients showed ictal trigeminal allodynia during the thermal challenge that was concurrent and positively correlated with μOR activation in the midbrain, extending from red nucleus to ventrolateral periaqueductal gray matter. These findings demonstrate for the first time in vivo the high μOR activation in the migraineurs' brains in response to their allodynic experience.